2004
DOI: 10.1016/j.ydbio.2003.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling is required for the differentiation of ES cells into neurectoderm

Abstract: Mouse embryonic stem cells can differentiate in vitro into cells of the nervous system, neurons and glia. This differentiation mimics stages observed in vivo, including the generation of primitive ectoderm and neurectoderm in embryoid body culture. We demonstrate here that embryonic stem cell lines mutant for components of the Hedgehog signaling cascade are deficient at generating neurectoderm-containing embryoid bodies. The embryoid bodies derived from mutant cells are also unable to respond to retinoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
7

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 64 publications
3
37
0
7
Order By: Relevance
“…Studies also indicate that Sonic Hedgehog promotes both the survival and proliferation of NSCs and neuroblasts during adult neurogenesis (Machold et al, 2003;Ahn and Joyner, 2005;Palma et al, 2005). Our initial studies, using ESCs carrying mutations in Hedgehog signaling components, suggested that this signal is critical for the differentiation of primitive ectoderm to neurectoderm (Maye et al, 2004). Our more recent analysis, using Hedgehog antagonists and the Sox1-GFP reporter system, has established two roles for Hedgehog signaling in ESC neurogenesis ( Fig.…”
Section: Hedgehog's Role In Proliferation Of Primitive Ectoderm-like mentioning
confidence: 84%
See 4 more Smart Citations
“…Studies also indicate that Sonic Hedgehog promotes both the survival and proliferation of NSCs and neuroblasts during adult neurogenesis (Machold et al, 2003;Ahn and Joyner, 2005;Palma et al, 2005). Our initial studies, using ESCs carrying mutations in Hedgehog signaling components, suggested that this signal is critical for the differentiation of primitive ectoderm to neurectoderm (Maye et al, 2004). Our more recent analysis, using Hedgehog antagonists and the Sox1-GFP reporter system, has established two roles for Hedgehog signaling in ESC neurogenesis ( Fig.…”
Section: Hedgehog's Role In Proliferation Of Primitive Ectoderm-like mentioning
confidence: 84%
“…ESC-derived embryoid bodies are similar to embryoid bodies derived from teratocarcinoma stem cells, first described by Stevens and Pierce (Pierce and Dixon, 1959;Stevens, 1959) and subsequently demonstrated to undergo a similar pattern of differentiation to isolated inner cell masses cultured in vitro (Martin et al, 1977). When mouse ESCs are removed from their feeder layer, and placed in suspension culture in the absence of the growth factor LIF, which promotes maintenance of the pluripotential state (Smith et al, 1988), they form aggregates, which within 2-4 days consist of an outer layer of hypoblastlike cells (extraembryonic visceral endoderm) surrounding an epiblastlike core (primitive ectoderm; Martin et al, 1977;Rathjen et al, 2002;Maye et al, 2004). At this stage, the embryoid body resembles the anterior prestreak stage embryo, with the epiblast-like core able to generate derivatives of all three primary germ layers; definitive endoderm, mesoderm, and ectoderm (Keller, 2005).…”
Section: Mimic the Embryo Environment: Embryoid Body Intermediates Mamentioning
confidence: 99%
See 3 more Smart Citations